“Food for a soldier” in the Polish army in 1807 - Srogosz, Tadeusz (Perspektywa stołu, 2023)
While stationed in the barracks or in the quarters, with regular deliveries, the daily food ration in the Polish army was sufficient. In field conditions, especially in winter and in the pre-harvest season, the nutrition of soldiers deteriorated rapidly. The country, devastated by war and requisitions, could not feed a large number of soldiers concentrated in a small area. The lack of detailed data does not make it possible to determine the amount of alcohol consumption by soldiers, but it can be assumed based on indirect sources that it was higher than in the entire society. The feeding of soldiers in the field hospitals was similar to the shape of the stationing.